2014
DOI: 10.1002/smll.201303942
|View full text |Cite
|
Sign up to set email alerts
|

A Nano‐Stripe Based Sensor for Temperature Measurement at the Submicrometer and Nano Scales

Abstract: Submicrometer dual-stripe temperature sensors made from a single piece of metal thin film (e.g., Pd) are developed. With the narrowest sensor being 900 nm in width, they show sensitivity of 1-2 μV/K for the full range of 10-300 K. The results confirm the size effect in Seebeck coefficient previously observed in microstripe sensors of the same device configuration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 24 publications
0
38
0
Order By: Relevance
“…This phenomenon was found following a brief power law of w − α , where w was the stripe width and α was a number close to one [41]. Since the length of 30–50 μm is two orders of magnitude larger than the mean free paths of the ordinary bulk metals tested in these studies, the results raised arguments [44,45].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…This phenomenon was found following a brief power law of w − α , where w was the stripe width and α was a number close to one [41]. Since the length of 30–50 μm is two orders of magnitude larger than the mean free paths of the ordinary bulk metals tested in these studies, the results raised arguments [44,45].…”
Section: Introductionmentioning
confidence: 92%
“…Recently, for the metallic thin film stripes of more than ten metals, such as Ni, Cr, Ti, Ta, Pd, and W, it was reported that, when the film thickness was kept at 80–100 nm, but the stripe width was changed from 100 micron to 30–50 μm, the thermopower of these stripes continuously showed measurable changes, and the size effect was enhanced when the stripe width was further reduced, all the way to 80 nm [19,40,41,42,43]. This phenomenon was found following a brief power law of w − α , where w was the stripe width and α was a number close to one [41].…”
Section: Introductionmentioning
confidence: 99%
“…Controlled freezing on the chip offers better survival (74% and 38% at holding temperatures of −25 °C and −40 °C, respectively) compared with direct freezing with liquid nitrogen vapor (27%). Likely a more accurate temperature sensor, such as the recently reported submicrometer and nano scale sensors (Huo et al, 2014), and feedback control on the microheaters, can improve cell survival (Li et al, 2010). …”
Section: Cooling and Warming: Programmable Freezing And Vitrificationmentioning
confidence: 99%
“…1,2 In this regard, accurate determination of temperature in the nano/micro scale regime, especially in microelectronic circuits, living cells, etc., [3][4][5][6][7][8] is essential to use noncontact optical based thermometers, which have its own advantages over conventional temperature measuring devices due to its noninvasive operations and inertness to various environment such as electrical or magnetic field or other harsh environments in the desired circumstances. [9][10][11] Among various optical thermometers, temperature induced change in different fluorescence parameters such as emission intensity, fluorescent intensity ratio (FIR), peak position, peak width, life time, etc.…”
Section: Introductionmentioning
confidence: 99%